Micronucleus and FTIR spectroscopy analysis as screening tests for HPV vírus detection (Research, Society and Development, 2022)
Human Papillomavirus (HPV) infection is the main precursor of cervical cancer. Pap Smear is the main diagnostic method of this neoplasm by cytological analysis, however presents a high rate of false-negative cases. This study aimed to verify if micronucleus (MN) frequency test and the Fourier Transform Infrared (FTIR) Spectroscopy analysis may be alternative useful techniques to detect HPV in cervical fluid. Fifty samples with normal cytology obtained from patients after cytopathological examination were divided into two groups based on the presence or absence of HPV by previous analysis of molecular biology. Of the fifty samples analyzed, 46% showed the presence of MN in the cells. The frequency of MN observed was higher in the samples with HPV positive and was related with age, use of oral contraceptives and use of alcoholic beverages (p